Proteoytic Activity and Swarming Growth of Proteus spp. Isolates. - Al- Ibadi, M. Ch. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Many clinical isolates of proteus spp. (30 isolates of P mirabilis and 30 isolates of P. vulgaris) from patients with urinary tract infections (UTIs) were examined for their ability to produce proteolytic enzymes and their ability to form swarming growth. Most (90%) of P. mirabilis and 60% of P. vulgaris isolates secreta proteolytic enzymes. A strong correlation was found between the ability of a strain to secreted proteases and it’s ability to form swarming growth. Non- swarming isolates invariably appeared to be non- proteolytic. However, some isolates (12 isolates of P. vagaries) were non- proteolytic even when they formed swarming growth